Optimal frequency/time combination of whole body vibration training for developing physical performance of people with sarcopenia: a randomized controlled trial. (October 2017) - Wei, Ning; Pang, Marco YC; Ng, Shamay SM; Ng, Gabriel YF
Objective: To determine whether frequency and exposure time to whole body vibration influenced its effects on physical performance in seniors with sarcopenia. Design: Randomized controlled trial Setting: A university sports training laboratory. Subjects: Eighty community dwelling seniors with sarcopenia were recruited. Interventions: Participants were randomly divided into 4 groups, namely, low-frequency (LG: 20Hz x 720s), medium-frequency (MG: 40Hz x 360s), high-frequency (HG: 60Hz x 240s) and control (CG: no extra training) for 12 weeks of whole body vibration training and 12 weeks of follow-up. Main measures: Assessments were done at baseline, mid-intervention, post-intervention, mid-follow-up, and final follow-up for five-repetition sit-to-stand, 10-meter walking test with self-preferred speed and timed-up-and-go test. Results: There was significant time × group interaction effect in timed-up-and-go test (F12, 304 = 3.333, effect size = 0.116, p < 0.001). Between-group differences in percentage change from baseline were significant between medium-frequency group and control group on all outcome variables after 12-week whole body vibration training (Five-repetition sit-to-stand test: 10.46 ± 2.28 (–16.12%), p = 0.008; 10-meter walking test: 1.05 ± 0.16 (11.18%), p = 0.04; Timed-up-and-go test: 11.32 ± 1.72 (–15.08%), p = 0.001). Conclusion: With the total number of vibrations controlled, the combination of 40Hz and 360s of whole body vibration has the best outcome on physical performance of people with sarcopenia.